Effect of a Habitual Late-Evening Physical Task on Sleep Quality in Neither-Type Soccer Players - Vitale, Jacopo A.; Banfi, Giuseppe; La Torre, Antonio; Bonato, Matteo (Frontiers in Physiology, 2018)
The aim was to investigate objective and subjective sleep quality, daytime tiredness and sleepiness in response to a late-evening High Intensity Interval Training (HIIT) session in neither-type soccer players that habitually trained late in the day. This is the first study that considered both athletes’ chronotype and habitual training time as crucial factors when assessing sleep quality in relation to an evening physical task. Methods: In this longitudinal, prospective, observational study,14 Italian soccer players were recruited (mean age: 26.1±4.5 years; height: 1.81±0.06 m; weight: 78.9±6.1 kg) and performed an extra-routine 4x4-min HIIT session at 09:00 p.m. Players used to train always between 09:00-11:00 p.m during the competitive season. All subjects wore an actigraph to evaluate their objective sleep parameters and a sleep diary was used to record subjective values of sleep quality, daytime tiredness, and daytime sleepiness. All data were analyzed as: the mean of the two nights before (PRE), the night after (POST 1), and the mean of the two nights after (POST 2) the extra-routine HIIT session. The subjects’ chronotype was assessed by the Morningness-Eveningness Questionnaire.. Results: All players were classified as N-types. None of the actigraph parameters nor the subjective values of sleep quality, tiredness, and sleepiness showed significant changes in PRE, POST1, and POST2. Conclusion: The results of our study added more information regarding sleep quality outcomes in response to a late-evening HIIT session. Athletic trainers and medical staff should always control for chronotype and habitual training time when assessing variations to sleep quality in athletes.